44 Quantifying the 5 year mortality of frequent attenders to the emergency department. Issue 12 (23rd November 2017) - Davison, Alexander; Boyle, Adrian; Hayhurst, Catherine
Abstract : Introduction: Frequent Attenders (FA) to Emergency Departments (ED) are a vulnerable population which we perceive to have a high morbidity and mortality. ED clinicians find this population challenging and they are at risk of being stigmatised. There has been little published work in the UK quantifying the risk of death in this population. Here we aim to quantify the 5 year mortality of this population and identify key risk factors. Methods: We identified a cohort of frequent attenders, defined as attending the ED 5 times or more between 1/4/2010 and 31/3/2011. We followed these patients via their electronic patient record from Cambridge University Hospital which is linked to the NHS spine. Overall mortality for the population has been calculated and we will produce a censored Kaplan-Meier survival estimate to account for patients we have been unable to follow up. Using a cox regression model we will analyse the impact of the chosen variables (age, sex, continued number of attendances to ED, and presence of a major physical or psychological illness or alcohol abuse) on mortality. Initial results: (pending full statistical analysis) 5 year mortality for the entire cohort was 24% and when limited to 16–65 year olds 5 year mortality was 11%. There will be a full risk factor analysis of this data available. Conclusion: Frequent Attenders to Addenbrooke's ED have a risk of death much greater than the normal population. A large proportion of the patients who died were very elderly and so 5 year mortality is less surprising but may suggest a need for further community care involvement to reduce ED attendance. The crucial finding is that the risk of death for adult FAs between the age of 16–65 is much higher than would be expected of the normal population. This indicates a need to treat this population with increased care.